GENE TRANSFER ON Betta imbellis THROUGH TRANSFECTION METHOD WITH DIFFERENT DNA CONCENTRATION - Eni Kusrini; Alimuddin Alimuddin; Mohammad Zairin; Dinar Tri Sulistyowati (Indonesian Aquaculture Journal, 2016)
Big size betta (Giant) have a high economic value compared to normal size betta, and over expression of growth hormone gene can produce giant fish.  As an initial step of giant transgenic betta productions, this study was conducted in order to obtain DNA plasmid concentration which provide higher hatching and survival rate of betta larvae.  Construction of PhGH pCcBA gene contains growth hormone gene of Siamese catfish (PhGH) and it is controlled by the CCBA promoter. Betta imbellis broodstocks were spawned naturally, and embryos were collected 1-2 minutes after spawning time. One hundred embryos were dipped in 2 mL of transfectan X-treme gene which containp CcBA-PhGH construction genes (50 µg/mL), on room temperature for about 30 minutes. Treatments on this study were different transfectant : DNA plasmid ratiosnamely:A (0,75 µL: 0,25 µL); B (0,75 µL : 0,50 µL); C (0,75 µL: 0,75 µL), D as Control 1(without transfectant, 0,25 µL DNA); E.as Control 2(0,75 µL transfectant, without DNA), and Fas control 3 (without transfectant and without DNA). Every treatments was repeated three times.  Transfection embryos were hatched on a container (1L Volume). Study results showed that hatching rate and larvae survival rate  (4 days after hatching) on treatment A were the same with the control, but slightly higher than B and C treatments. PCR analysis with DNA template showing that PhGH gene were found on embryos and larvae (pooled sample) of treatment A, B and C. Furthermore, RT-PCR analysis showing the existence of mRNA PhGH expression on embryos and larvae (pooled sample). Therefore, embryo transfection with transfectant ratio 0,75 µL and  DNA 0,25 µLshowing the best results.